Toxicological Risk Assessment of the Accidental Ingestion of a Honeybee (Apis mellifera L.) Present in Food - Marinho, Jéssica Baeça Rezende; Soto-Blanco, Benito (Frontiers in Veterinary Science, 2020)
The aim of the present work was to evaluate the possible risk of toxic effects due to the ingestion of a honeybee (Apis mellifera L.) accidentally present in food. The amount of venom present in a bee is considered insufficient to induce detectable toxic effects in a person who ingests it by accident, and various components of the venom are destroyed by gastric secretions. However, despite the rare frequency, there is a risk of the ingestion of a bee causing an allergic reaction to some components of the venom in sensitized individuals. In addition, pollen carried by a bee may cause an allergic reaction in a sensitive individual. Thus, the accidental ingestion of a bee present in a food does not pose the risk of toxic effects for the majority of the population, but may promote allergic reactions in susceptible individuals.